Accuracy assessment of old large-scale maps and reducing positional error in land use change analyses - Darina Kratochvílová; Jiří Cajthaml (Scientific Reports)
Abstract Old large-scale maps are a very valuable source of historical data and have a place in landscape studies, especially when researching smaller areas, such as municipalities or cadastres, where they allow work at the level of land parcels. The purpose of this study was to verify the positional accuracy of large-scale maps used in landscape analyses and to test the possibility of eliminating the influence of positional inconsistency of map sources on the results of analyses. The achieved values of the mean positional errors for the historical data models from the mid-19th and mid-20th centuries are in the range of three to four metres for the model areas, which is highly accurate considering the scale values of the old maps used, confirming the suitability of these maps for landscape studies. Narrow residual polygons, referred to as sliver polygons, arise during overlay operations because of positional errors in old maps can affect the results of the analysis. Different methods for removing sliver polygons were proposed and tested by comparing the selected results of the spatiotemporal analysis. The methods reduced the false change areas, which was most evident in the change maps. The change maps after using the appropriate method better reflected the true changes.